Observation of intermultiplet transitions in Sm(Fe11Ti) by inelastic neutron scattering - COEY, JOHN MICHAEL DAVID (American Physical Society, 1990)
Magnetic neutron spectroscopy of SMFe11Ti reveals a dispersionless electronic excitation corresponding to transitions between levels of the exchange-split ground- and first-excited-state multiplets of the Sm3+ ion. The observed excitation energy of 175.5 meV at T=20 K may be accounted for in the framework of an exchange and crystal-field model by assuming a bare spin-orbit splitting of 129 meV for the J=5/2 and 7/2 multiplets. The neutron spectroscopy data are explained with the same parameters used to fit the experimental magnetization curves of single-crystal SmFe11Ti.
PUBLISHED
Keywords: Physics